Empowering Fijian farmers with mobile apps - Daunivalu, Jiu (Technical Centre for Agricultural and Rural Cooperation, 2018)
Restructuring the way Fiji’s agricultural sector operates has allowed the Fiji Crop and Livestock Council (FCLC) to build a database of its farmers, and to focus on a plan to empower them through technological innovations. With a more efficient engagement structure in place, the Council launched a mobile app in 2013 to disseminate useful information to rural farmers across the country. The app is helping farmers to increase their productivity and profitability. Despite these benefits, however, maintaining the mobile technology has its challenges.